Association between lower phase angle and chronic kidney disease progression in type 2 diabetes patients - Low, Serena (2024)
Introduction: Phase angle (PhA), derived from bioelectrical impedance analysis (BIA), is the angle of vector determined by the body’s resistance and reactance. It indicates cellular integrity and hydration status. Though extracellular volume excess was associated with chronic kidney disease (CKD) progression, the association between PhA and CKD progression is unknown. Matrix metalloproteinase-2 (MMP-2) is a member of zinc-dependent endopeptidase family and promotes renal interstitial fibrosis. We investigated association between PhA and CKD progression, and whether the association was through MMP-2 in patients with type 2 diabetes mellitus (T2DM). Method: We conducted a prospective study on 1,078 patients with T2DM (mean age 58.9±9.1 years). PhA was measured using BIA. CKD progression was defined as ≥25% decrease in estimated glomerular filtration rate (eGFR) from baseline with deterioration across eGFR categories. Multiplex immunoassay was used to quantitate MMP-2. We examined association between PhA and CKD progression using Cox proportional hazards model, adjusting for demographics, clinical parameters and medications. Results: Over 8.6 years of follow-up, 43.7% of participants had CKD progression. Compared to tertile 3 PhA (higher level), tertiles 1 and 2 PhA were associated with higher hazards of CKD progression, with corresponding unadjusted hazard ratios (HRs) of 2.27 (95% confidence interval [CI] 1.80–2.87, P<0.001) and 1.57 (95% CI 1.24–2.01, P<0.001). The positive association between tertiles 1 and 2 PhA with CKD progression persisted in the fully adjusted model with corresponding HRs of 1.71 (95% CI 1.30–2.26, P<0.001) and 1.46 (95% CI 1.13–1.88, P=0.004). MMP-2 accounted for 14.7% of association between tertile 1 PhA and CKD progression. Conclusion: Our findings revealed a previously unobserved association between BIA-derived lower PhA and CKD progression through MMP-2 in patients with T2DM.